Implementation of Organizational Theory in Managing Work Structure and Culture in the Digital Era - Cindy Charoline; Melina Budiarti; Eveline Hongo; Purwadhi Purwadhi; Yani Restiani Widjaja (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation has pushed organizations to adjust their work structures and cultures to face challenges and take advantage of opportunities in the digital era. Rapid technological changes not only change the way of working, but also demand adaptation in the structural and cultural aspects of the organization to remain competitive and relevant. This study aims to analyze the implementation of organizational theory, especially the structural and cultural approaches of the organization, in managing organizations amidst the dynamics of the digital era. This study uses a qualitative approach with a case study method in several public and private sector organizations that are undergoing digital transformation. The results of the study show that organizations that successfully apply organizational theory adaptively tend to be able to build more flexible, collaborative, and technology-based structures. In addition, a work culture that supports innovation, continuous learning, and open communication are key factors in supporting the digital transformation process. In the context of structure, flat organizational models and decentralized decision-making have proven to be more responsive to change. Meanwhile, an inclusive work culture that is adaptive to technology and encourages active participation from all members of the organization can accelerate the integration of digital technology into daily work activities. The conclusion of this study is that the implementation of organizational theory in the aspects of work structure and culture plays a strategic role in the success of organizations in the digital era. The ability of organizations to balance formal structures with flexibility and develop an adaptive culture is key to sustainability and competitiveness amid ongoing digital disruption.